Geotourist attractions of the Central Sudetic Geostrada // Atrakcje geoturystyczne Geostrady Środkowosudeckiej - Bartuś, Tomasz; Mastej, Wojciech; Łodziński, Marek (Geotourism/Geoturystyka)
The aim of the paper is presentation of a geological and landscape studies with inventarization of the objects of abiotic nature heritage located along the central part of proposed trail “The Leszek Sawicki Sudetic Geostrada”. The Central Sudetic Geostrada extends from the Kowary Pass in the west to the Płoszczyna Pass near Stronie Śląskie in the east. Total length of this sector of Geostrada is about 200 km, in which about 60 km in the Czech Republic. The principle is to run the trail in such a manner that attractive geosites and other interesting tourist destinations fall into the 10-kilometers-wide zone (± 5 km zone from both sides of the road). First of all, these are groups of sandstone monadnocks in the Table Mts., but also numerous geosites close to Lądek Zdrój: caves, including the famous ”Bear Cave”, mineral waters, gneiss tors, the famous waterfall on the Wilczka River, numerous marble and basalt quarries and relics of old mining camps. // Celem niniejszej pracy jest prezentacja studium geologiczno-krajobrazowego z inwentaryzacją obiektów dziedzictwa przyrody nieożywionej dla obszaru Sudetów, wzdłuż środkowej części proponowanej trasy turystyczno-rekreacyjnej, nazwanej Geostradą Sudecką im. Leszka Sawickiego. Geostrada Środkowosudecka ograniczona jest przełęczami: Kowarską na zachodzie i Płoszczyna na wschodzie, koło Stronia Śląskiego. Liczy łącznie ok. 200 km, w tym ok. 60 km w Czechach. Jest ona prowadzona w taki sposób, by w wąskim pasie o szerokości 10 km (5 km po obu stronach Geostrady) znalazły się atrakcyjne obiekty geoturystyczne w przypadku środkowosudeckiego odcinka Geostrady, są to przede wszystkim zgrupowania piaskowcowych ostańców erozyjnych w Górach Stołowych, a także liczne obiekty w okolicach Lądka Zdroju: jaskinie wypreparowane w marmurach, w tym najsłynniejsza Jaskinie Niedźwiedzia, wystąpienia wód mineralnych, skałki gnejsowe, sławny wodospad Wilczki, liczne kamieniołomy marmurów i bazaltów oraz ślady działalności górniczej.